MCDST guide to supporting users and troubleshooting desktop applications on a microsoft windows XP operating system: - Carswell, Ron (Thomson, 2005)
Students will master the objectives for the new Microsoft Desktop Support Technician exam # 70-272 using a hands-on approach created specifically for them.